ANALISIS WILCOXON MATH PAIR TEST PADA PENERAPAN MATAKULIAH ENTREPRENEURSHIP TERHADAP MOTIVASI MAHASISWA UNTUK MENJADI ENTREPRENEUR SUKSES - Suha rini (Jurnal Akrab Juara, 2019)
In this study the author wants to know whether there are differences in motivation between students before taking entrepreneurship courses along with activities that support them, namely SWE and EF and afterwards. The study was conducted on BSI University students by taking a sample of 100 people. The analytical tool used is the Wilcoxon Math Pair Test Analysis technique. The results of the analysis show the value of Asymp. Sig. (2-tailed) is 0,000. This value is smaller than (<0.05), so that the alternative hypothesis Ha can be accepted means that there are differences in student motivation values ​​before and after taking Entrepreneurship courses and supporting activities at BSI University namely SWE, and EF. The existence of these differences shows that the application of courses and supporting activities has a positive impact on the motivation of students to become successful entrepreneurs.